Essential oils as vespid wasp repellents: Implications for their use as a management strategy. (14th April 2019) - Yossen, María B.; Lozada, Mariana; Kuperman, Marcelo N.; González, Silvia; Gastaldi, Bruno; Buteler, Micaela
Abstract: Recently, plant‐based repellents have been proposed as a potential alternative to classic pesticides against pest wasps, in certain scenarios. Here, the repellent effect of Dysphania multifida essential oil and one of its main terpenoid components, α‐terpinene, were tested under field conditions with natural populations of wasps in Patagonia Argentina. D. multifida essential oil (paico), as well as α‐terpinene, repelled V. germanica wasps in the field. A strong avoidance of food baits treated with the essential oil or α‐terpinene was observed in choice and no‐choice tests. In no‐choice tests, the time it took wasps to arrive at the bait was significantly greater in treated baits than in control baits. Also, the total number of arriving wasps in 30 min was significantly greater in untreated baits in comparison with treated baits, under similar environmental conditions and wasp density. As the wasps' flight season progressed, wasp density and motivation for proteinaceous food sources increased. This was evidenced by a greater total number of wasps in untreated baits with time. On the contrary, the number of wasps in treated baits remained low throughout the peak season. Both the paico essential oil and the α‐terpinene act as powerful repellents for V. germanica wasps, generating an avoidance response to treated food sources. Thus, these compounds have potential to be used as repellents to prevent wasps' approaches and foraging, when applied in close proximity to a food source.